PEMBERDAYAAN PETANI DESA PAJANGAN LAMONGAN MELALUI TEKNOLOGI PEMBUATAN PUPUK ORGANIK DAN APLIKASINYA - Qibtiyah, Mariyatul; Ni’mah, Khoirotun; Mayasari, Intan; Mubarok, M Rifqi; Bukhori, Imam (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Harvest residues in the form of straw and husks are abundantly found around agricultural and milling land in Pajangan Village, Sukodadi Lamongan. In addition, livestock waste in the backyards of people who have livestock has not been utilized. This community service activity is based on farmers’ ignorance of how to make organic fertilizer by utilizing waste around their land. This activity aims to provide direct learning and practice to farmers in the form of training in making solid and liquid organic fertilizers from harvest residues and livestock waste and their applications. The implementation of this community service began in June to August 2024. This activity was carried out for farmers who are members of the Harapan Farmers Group Association, Pajangan Village, Sukodadi, Lamongan. The activities carried out were observation, socialization, training activities and activity evaluation. The results of this activity are that farmers have the knowledge and skills in making solid and liquid organic fertilizers and how to apply them to their land and plants. So that farmers can make their own organic fertilizers to be applied to their land and plants to support organic farming activities.